415 Prognostic factors for recurrence in carcinoma endometrium. (13th November 2020) - Prakasan, A; Dhas, M; Kumar, A; Mathews, S; Joseph, J; Krishna, J; ,; ,; James, FV
Abstract : Objective: Incidence of endometrial cancer is on the rise in India. Although there have been significant advances in understanding of endometrial cancer biology, these factors are not yet included in routine management of patients. The aim of the study was to identify prognostic factors for risk stratification and offering judicious adjuvant therapy. Methods: Retrospective analysis of data of patients with carcinoma endometrium registered at Regional Cancer Centre, Thiruvananthapuram from January 2009 to December 2013 was done. Various patient, tumor and treatment related factors were analyzed for its effect on recurrence. Survival estimates were generated using Kaplan –Meier method. Univariate analysis was done using Chi-square and Fisher's exact tests and multivariate analysis was done using Cox regression model. The statistical analysis was done using SSPS software version 11. Results: The median follow up of 642 patients was 95 months (range 3–178 months).There were 432 stage 1 (67%), 100 stage II ( 15.57%), 108 stage III (16.8%)and 2 stage IVa patients (0.3%). The five-year disease free survival (DFS) was 82.1%. Prognostic factors for DFS on multivariate analysis were age> 60 years, high grade tumor, advanced stage, deep myometrial invasion, cervical stromal invasion, and negative Progesterone Receptor (PR) status. Cervical stromal invasion, negative PR status, no adjuvant treatment were associated with pelvic failure. Conclusion: The predictive and prognostic factors for Carcinoma endometrium is similar to those published in developed countries.